Upaya Melestarikan Tradisi Keagamaan Aswaja (Studi Kasus Pondok Pesantren al-Falah Sumber Gayam Pamekasan) - Mas’udi (JSP: Jurnal Studi Pesantren, 2023)
Various religious denomination and movements, which often prioritise extremism and radicalism, can cause disintegration in society, and can even damage the comprehension of Ahlussunnah wal Jamaah. The efforts of pesantren to straighten out the creed are very necessary, because up to this moment, those who play an active role in the midst of society in disseminating Aswaja are pesantren and pesantren alumni. The focus of this research is to examine what forms of Aswaja religious traditions practised by Pondok Pesantren al-Falah Sumber Gayam, as well as how efforts are made in preserving Aswaja religious traditions in Kadur village, Kadur District, Pamekasan Regency. This study is a field research type. The data collection instruments used are interview, observation, and documentation. Those are then processed using descriptive qualitative methods. In this approach, researcher creates complex images, examines words and detailed reports from the views of respondents, and conducts studies in experienced situations. Based on the results of the analysis that has been carried out, it shows that the forms of religious traditions practiced by this pesantren include: istighatsah, giving good testimony for the corpse, yasinan, tahlilan, grave pilgrimage, rajaban, tawasul, selamatan, rabu wekasan, manaqiban, marhabanan. Meanwhile, the efforts of this pesantren in purpose of preserving the religious traditions of Ahlussunnah wal Jamaah are first, distributing guidebooks for the implementation of Ahlussunnah wal Jamaah religious traditions to community leaders and alumni. Second, Continuously maintaining this daily behavior to teach this tradition to the students or the surrounding community. Third, holding a question and answer session media in the learning classical book with alumni and the community in an effort to minimise the influence beyond the Ahlussunnah wal Jamaah doctrines that try to distort beliefs in maintaining the traditions of Ahlussunnah wal Jamaah of the Kadur Village community.